An evaluation of the effectiveness of protected areas in Thailand - Minerva Singh (Elsevier, 2021)
Thailand is a biodiversity hotspot and home to over 1000 bird species, 15,000 plant species, and five of the World Wildlife Fund’s Global 200 Ecoregions of ecological significance. To preserve their unique ecosystems, the Thai government has established and maintained protected areas (PA) which in 2020, are estimated to cover 19% of Thailand’s land area. The success of these areas in preserving biodiversity to date is somewhat ambiguous. Using gap analyses, we evaluated the extent and adequacy of coverage provided by these PAs for the preservation of these unique ecoregions, to threatened amphibian, bird, and mammal species richness hotspots and at a range of altitudes within Thailand.Regionally, the Indochina dry forests, Northern Khorat Plateau moist deciduous forests and Malaysian Peninsula rainforests are all under-represented. Though opportunities exist for their protection through marine designation, mangrove and wetland ecosystems are also seriously under-represented in the current spatial layout and network connectivity of Thailand’s protected area system. Highland areas (>750 m elevation) are well-protected, in contrast to the lower altitude areas where human and agricultural pressures are higher. Hotspots of threatened birds located in the northern and southern regions of Thailand, as well as most of the central threatened mammal hotspot, are inadequately covered (<10%). The current PAs could be expanded with a focus on these key areas, or further PAs created to address these gaps in provision. The Thai PA network is also highly fragmented and, in addition to increasing the area covered, contiguity and connectivity of the network should be considered. With human population expansion in the central lowland area particularly, there will be challenges and trade-offs to be negotiated along with enforcement within existing areas. We hope, though, that the results of this study can aid policymakers in improving Thai conservation effectiveness.